The Predictive Value of the Pentraxin 3 Concentration in Cumulus Cell Culture Media for the Embryo Implantation - Irez, Tulay; Sahin, Yavuz; Malik, Eduard; Guralp, Onur (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: Many studies on the interrelation of cumulus cells and oocytes, and research on cumulus protein factors continue. This study aims to investigate the relationship of Pentraxin 3 level with embryo implantation in the cumulus culture fluid. STUDY DESIGN: A total of 31 women with idiopathic infertility who underwent intracytoplasmic sperm injection treatment were prospectively evaluated. Cell suspensions containing 5 million/mL cumulus cells were obtained post-hyase and incubated for 24 hours in a culture medium. A possible association between the culture media Pentraxin 3 concentrations and embryo implantation was analyzed. RESULTS: The cumulus cell culture media Pentraxin 3 concentrations were significantly higher in the pregnant group compared to the non-pregnant group (98.9 ng/mL vs 53.2 ng/mL, respectively, p=0.005). There was a significant positive correlation between the culture media Pentraxin 3 concentrations and embryo implantation (r=0.500, p=0.005). The culture media Pentraxin 3 concentration was a significant predictor for successful embryo implantation (AUC=0.845, p=0.006). A cut-off value of 64.25 ng/mL had an 86% sensitivity and 80% specificity to predict embryo implantation. There was no pregnancy under the cut-off value of 60 ng/mL, whereby seven women had good quality grade 1 oocytes according to the traditional morphological criteria. CONCLUSION: The cumulus cell culture medium Pentraxin 3 concentration was predictive for successful embryo implantation. Low Pentraxin 3 levels (<60 ng/mL were associated with failure of conception.